Synthetic Approaches for Accessing Pseudaminic Acid (Pse) Bacterial Glycans. (26th February 2020) - Flack, Emily K. P.; Chidwick, Harriet S.; Best, Matthew; Thomas, Gavin H.; Fascione, Martin A.
Abstract: Pseudaminic acids (Pses) are a group of non‐mammalian nonulosonic acids (nulOs) that have been shown to be an important virulence factor for a number of pathogenic bacteria, including emerging multidrug‐resistant ESKAPE pathogens. Despite their discovery over 30 years ago, relatively little is known about the biological significance of Pse glycans compared with their sialic acid analogues, primarily due to a lack of access to the synthetically challenging Pse architecture. Recently, however, the Pse backbone has been subjected to increasing synthetic exploration by carbohydrate (bio)chemists, and the total synthesis of complex Pse glycans achieved with inspiration from the biosynthesis and subsequent detailed study of chemical glycosylation by using Pse donors. Herein, context is provided for these efforts by summarising recent synthetic approaches pioneered for accessing Pse glycans, which are set to open up this underexplored area of glycoscience to the wider scientific community. Abstract : Sugars to order : A summary of work in the field of pseudaminic acid (Pse) synthesis is provided. This non‐mammalian sugar is of increasing biological importance as an essential component in cell‐surface glycoconjugates of a number of pathogenic bacteria. Pioneering studies into biosynthesis of Pse5Ac7Ac have provided inspiration to carbohydrate chemists.